Long-Term Results of Bilateral Medial Rectus Muscle Recession in Children with Developmental Delay. (2nd January 2016) - Zehavi-Dorin, Tzukit; Ben-Zion, Itay; Mezer, Eedy; Wygnanski-Jaffe, Tamara
ABSTRACT: Purpose : To assess the long-term results of a reduced amount of medial rectus recession in children with esotropia and developmental delay. Methods : A retrospective chart analysis of 42 children with developmental delay who had undergone surgery for esotropia during a 20-year period in a large referral center was performed. The pre- and postoperative angle of deviation was calculated for each subject as the mean of distant and near angles measured by a cover test or the Krimsky measurement. Surgical success was categorized as esotropia or exotropia of ≤10 prism diopters (PD). The main outcome measure was a stable surgical result after several years of follow-up. Results : The chart review identified 42 children who met inclusion criteria, with a mean age of 2.9 years (range, 0.8-10 years). The mean angle of esotropia prior to surgery was 44.29 ± 13.9 PD (range 20-80 PD). All patients had bilateral medial rectus muscle recessions, with a mean surgical dosage of 5.04 ± 0.62 mm per muscle, on average 0.66 mm less than the standard amount. The average postoperative follow-up was 4.6 years (median 3.67 years, range 8 months-15 years). Twenty-four children (57%) achieved surgical success, 13 (31%) were undercorrected, and 5 (12%) were overcorrected. Ten of the 18 with an unsuccessful surgical outcome underwent a second procedure. The overall surgical success rate for all patients after all procedures was 71%. Conclusions : The main reason for surgical failure after bilateral medial rectus muscle recession (BMR) in developmentally delayed children remains residual esotropia. However, with time, more patients demonstrated consecutive exotropia. Although it is difficult to achieve a stable long-term ocular alignment in children with developmental delay, satisfactory results may be achieved with additional surgical procedures. The optimal amount of primary recession and whether to perform the surgical schedules according to the Parks tables or to reduce the amount of the recession when operating on children with developmental delay is still debatable.